Analisa Faktor Risiko Penyebab Kejadian Penyakit Gagal Ginjal Kronik (GGK) Di Ruang Hemodialisa RS Dr. Moewardi - Siti Purwati ((JKG) Jurnal Keperawatan Global, 2018)
Background: Chronic renal failure is a disease that affects many people of Indonesia. CRF is caused by several risk factors such as age, sex, smoking history, history of hypertension, history of diabetes, history of consumption analgesic / NSAID, history of energy drink supplement consumption. Based on medical record data RS Dr. Moewardi Surakarta number of patients with chronic renal failure in 2015 was 1023 patients. The purpose of this research was to analyze the risk factors associated with disease occurrence of CRF in RS Dr. Moewardi. Method: Research design used in this study design was descriptive analytic with cross-sectional design. The total sample of 60 respondents from patients with CRF in Space Hemodialysis in RS Dr. Moewardi in March and April 2016 used univariate frequency distribution, bivariate chi-square, multivariate logistic regression. Result: this research showed the highest frequency distribution is equal to the age of more than 60 years of 91,7%, male gender 53,3%, 53,3% smoking history, history of hypertension of 75,0%, a history of DM 55 %, a history of consumption of analgesics/NSAIDs 53,3%, a history of consumption of 90,0% supplement drink. Bivariate analysis showed significant association between the occurrence of CRF stage 5 with age (p-value 0.039), gender (p-value 0.036), history of smoking (p-value 0.036), hypertension (p-value 0.021), DM (p-value 0.016), consumption of analgesics/ NSAID (p-value 0.001), supplement beverage consumption (p-value 0.008 ). Results of multivariate analysis found the most dominant factor in the incidence of CRF stage 5 is a history of consumption of supplement drink with OR = 35.791. risk factors most dominant factor is a history of consumption of beverage supplements.